Mid-Face Degloving: An Alternate Approach to Extended Osteotomies of the Midface. Issue 1 (January 2017) - Parameswaran, Anantanarayanan; Jayakumar, Naveen Kumar; Ramanathan, Manikandhan; Sailer, Hermann F.
Abstract : Abstract: Extended osteotomies for mid-face advancement require generous exposure of the anterior maxilla, nasal bones, infraorbital rims, orbital floor, zygoma, and the anterior third of the zygomatic arches. This cannot be obtained with an exclusive transoral approach. Hence, the surgeon is usually compelled to utilize supplemental cutaneous incisions that are a compromise on the purpose behind a cosmetic surgery. In order to alleviate the need for such compromise, the authors advocate the mid face degloving approach for extended osteotomies at Lefort II and Lefort III levels. Mid face degloving involves a combination of circumvestibular incision, with inter cartilaginous and transfixation components from a nasal incision. The authors have utilized this technique for 9 patients and documented favorable results. The purpose of this paper is to focus the utility of this approach in orthognathic surgery and promote this as a viable alternative to traditional approaches in surgery of the mid face because of the absence of external scars.